DEVELOPMENT MODEL DA’WAH OF MILLINEAL IN THE YUK NGAJI COMMUNITY - Abqorina Abqorina; Faisal Faisal (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
The most non-formal education that has emerged in the midst of society is Islamic educational institutions in the form of Majlis Ta'lim. Majlis Ta'lim or religious community, one of which is the hijrah community, is called the hijrah movement called YukNgaji. This hijrah movement is a hijrah community which focuses on a group of millinial children who want to change their lives by leaving the bad things that happen by becoming more obedient to Allah SWT. This research uses a qualitative method using a phenomenological approach by exploring the meaning in depth related to the educational curriculum model in the YukNgaji community in Bintaro. The development of millinneal da'wah in the Yuk Ngaji community by utilizing technology and information in delivering da'wah content in the form of da'wah of akidah, fiqh and morals. Keywords: Non-formal education, Majlis Ta'lim, and YukNgaji Community.